2012
DOI: 10.1584/jpestics.d11-018
|View full text |Cite
|
Sign up to set email alerts
|

Fipronil resistance in Sogatella furcifera: Molecular cloning and functional expression of wild-type and mutant RDL GABA receptor subunits

Abstract: The whitebacked planthopper Sogatella furcifera is a serious pest of rice that has developed fipronil resistance in Asia. We found a novel R340Q mutation in the cytoplasmic loop between M3 and M4 of the S. furcifera RDL γ-aminobutyric acid (GABA) receptor subunit (SF-RDL). The R340Q mutation was found in clones carrying the A2′N mutation, which was previously implicated in fipronil resistance and suggested to be a heterozygous mutation. To investigate the influence of mutations, Drosophila Mel-2 cells were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 36 publications
(48 reference statements)
4
42
0
Order By: Relevance
“…[4][5][6] To date, A2′S, A2′G, and T6′L mutations have been reported to be associated with cyclodiene resistance in various insect species. [7][8][9][10][11][12][13][14][15] A2′S and A2′G mutations show a low level of crossresistance to fipronil, 11) and the A2′N mutation was suggested to confer fipronil resistance in the major rice pests white backed planthopper Sogatella furcifera 16,17) and small brown planthopper Laodelphax striatellus. 18) Since insects have developed resistance to phenylpyrazoles and cyclodiene organochlorines, it is necessary to discover new insecticides that are effective against these insecticide-resistant pests.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] To date, A2′S, A2′G, and T6′L mutations have been reported to be associated with cyclodiene resistance in various insect species. [7][8][9][10][11][12][13][14][15] A2′S and A2′G mutations show a low level of crossresistance to fipronil, 11) and the A2′N mutation was suggested to confer fipronil resistance in the major rice pests white backed planthopper Sogatella furcifera 16,17) and small brown planthopper Laodelphax striatellus. 18) Since insects have developed resistance to phenylpyrazoles and cyclodiene organochlorines, it is necessary to discover new insecticides that are effective against these insecticide-resistant pests.…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of resistance is low. 14) We found A2′N mutation in the RDL GABA receptor in serious rice pests, the white backed planthopper Sogatella furcifera, [18][19][20] and the small brown planthopper, Laodelphax striatellus, 21) and suggested that this mutation confers fipronil resistance. Thus, insects have developed resistance to first-and second-generation noncompetitive antagonists that target insect RDL GABA receptors.…”
Section: Introductionmentioning
confidence: 85%
“…By contrast, the RDL GABA receptors were not inhibited at all by 3 µM fipronil in cells co-transfected with wild-type and A2′N⋅R340Q double mutant genes. 15) These results suggests that the A2′N⋅R340Q double mutation confers a higher level of resistance to fipronil than the A2′N single mutation in the heterozygous expression of the wild-type and mutant S. furcifera RDL GABA receptor subunit genes.…”
Section: Mechanisms Of Fipronil Resistance In Sogatella Furciferamentioning
confidence: 91%
“…A membrane potential assay showed that the IC 50 value of fipronil for the wild-type S. furcifera RDL GABA receptor subunit homomer was 79 nM. 15) RDL GABA receptors were inhibited by up to 40% with 3 µM fipronil in cells co-transfected with wild-type and A2′N mutant genes. By contrast, the RDL GABA receptors were not inhibited at all by 3 µM fipronil in cells co-transfected with wild-type and A2′N⋅R340Q double mutant genes.…”
Section: Mechanisms Of Fipronil Resistance In Sogatella Furciferamentioning
confidence: 99%